2014
DOI: 10.1093/heapol/czu004
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behaviour and the related household out-of-pocket expenditure for chronic non-communicable diseases in rural Malawi

Abstract: Malawi is facing a rising chronic non-communicable disease (CNCD) epidemic. This study explored health seeking behaviour and related expenditure on CNCDs in rural Malawi, with specific focus on detecting potential differences across population groups. We used data from the first round of a panel household health survey conducted in rural Malawi between August and October 2012 on a sample of 1199 households. Multinomial logistic regression was used to analyse factors associated with health seeking choices for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 39 publications
5
38
1
Order By: Relevance
“…Even when the costs of hospital consultation, laboratory examination and buying medication from hospitals can be covered, the decision to do so can be postponed, depending on other factors, most prominently the perceived severity of the disease. Other studies have reported a similar strategic use of available resources [47–51]. Perceived severity is an obvious incentive for hospital-based action [22].…”
Section: Discussionmentioning
confidence: 79%
“…Even when the costs of hospital consultation, laboratory examination and buying medication from hospitals can be covered, the decision to do so can be postponed, depending on other factors, most prominently the perceived severity of the disease. Other studies have reported a similar strategic use of available resources [47–51]. Perceived severity is an obvious incentive for hospital-based action [22].…”
Section: Discussionmentioning
confidence: 79%
“…Since healthcare expenditures were non‐normally distributed, 5% trimmed means (arithmetic mean after eliminating 5% each of the smallest and largest cases) were used. This leads to an inevitable but negligible reduction in the sample size (Osborn, ; Wang et al, ). Mann–Whitney test was used as a test of significance.…”
Section: Methodsmentioning
confidence: 99%
“…In 2010, the government expanded the EHP to also include health interventions targeting the most common CNCDs, such as screening, prevention, and treatment of cardiovascular diseases, diabetes, and certain cancers (breast cancer, cervical cancer) [21]. As shown in our previous work, however, health service utilization by people suffering from any of these CNCDs remains rather poor [23]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, there are 6 private for-profit facilities. Details of the sampling procedures for the panel household survey have been described elsewhere [23]. In brief, given that the ultimate purpose of the panel was to evaluate the impact of a micro-health insurance scheme to be launched by the local Savings and Credit Cooperative (SACCO), the panel included both households where at least one person was a SACCO member ( n = 691) and households where no person was a SACCO member ( n = 525).…”
Section: Methodsmentioning
confidence: 99%